KAJIAN PENGEMBANGAN DAN PENGELOLAAN POTENSI EKOWISATA BAHARI DI KECAMATAN TUHEMBERUA KABUPATEN NIAS UTARA PROVINSI SUMATERA UTARA - Betzy Victor Telaumbanua; Deni Efizon; Windarti Windarti (Berkala Perikanan Terubuk, 2017)
This research was conducted on February to April 2017 The study areas Marisa Beach, Tanayao Beach, Botogawu Beach and Fofola Indah Beach. A survey method was applied and data obtained from 189 respondents were descriptively analyzed.  The aimed of this study was to review the objects and issues of marine ecotourism has been conducted from February to April 2017. The study areas Marisa Beach, Tanayao Beach, Botogawu Beach and Fofola Indah Beach. A survey method was applied and data obtained from 189 respondents were descriptively analyzed.      Based on research results Tuhemberua Subdistrict is potential and suitable to be developed as marine ecotourism area. Activities that can be developed are swimming, sunbathing, beach recreation, water sports and boating. The main problems identified are as follow: less participation of stakeholders in developing the marine ecotourism, less attention from local governments in providing adequate facilities in each marine ecotourism object.  Scores of Tourism Suitability Index (TSI) was 97.44-100% and scores of Carrying Capacity Area was 222-318 persons/day. The highest TSI score was obtained in the Botogawu Beach and Fofola Indah Beach (100%) and the highest Carrying Capacity score was in the Fofola Indah Beach (318 persons/day). There were three main strategies for developing the marine ecotourism activities, namely anticipating and handling the threat of coastal abrasion and degradation, cooperation with travel agency as well as coastal conservation efforts.